Association between behavioural factors and BMI-for-age among early adolescents in Hulu Langat district, Selangor, Malaysia - Woon, Fui Chee; Chin, Yit Siew; Mohd Taib, Mohd Nasir (Elsevier, 2015)
Objective: This paper investigates the association between behavioural factors and BMI-for-age among early adolescents (10–11 years old) in Hulu Langat district, Selangor. Methods: This cross-sectional study was conducted among 333 primary school students. Body weight and height of the students were measured and their BMI-for-age was calculated. Eating behaviours, energy intake, energy expenditure, physical activity, and screen time were assessed using the Eating Behaviours Questionnaire and a 2-day dietary and physical activity recall, respectively. Data were analysed using multiple linear regression analysis. Results: The prevalence of overweight and obesity (28.2%) was about twice the prevalence of thinness (11.1%). The mean energy intake and energy expenditure of the students was 1772 ± 441 kcal/day and 1705 ± 331 kcal/day, respectively. Three in five of the students (60.1%) skipped at least one meal and 98.2% snacked between meals daily. A majority of them (55.3%) were sedentary. Low energy intake (p < 0.05) and low energy expenditure (p < 0.05) were associated with high BMI-for-age. Energy expenditure (β = −0.033) and energy intake (β = −0.090) significantly explained 65.1% of the variances in BMI-for-age (F = 119.170, p < 0.05). Conclusion: These findings suggested that promoting healthy eating and active lifestyle should be targeted in the prevention and management of obesity among early adolescents.